The influence of the distance between the donor-acceptor groups of polymethine dyes on their photovoltaic properties - Seliverstova, E.; Ibrayev, N. (IOP publishing LTD, 2018)
Spectral-luminescent and photovoltaic properties of polymethine dyes of various structures are studied. It is shown that an increase in the length of the methylene chain between the active chromophores leads to a red-wave shift of the absorption and fluorescence spectra. Significant changes in the absorptivity and lifetime of fluorescence do not occur in this case. The best photovoltaic parameters have cells sensitized with shorter dye molecules. It is shown,that for a longer dye the resistance associated with electron recombination on the TiO2/electrolyte surface is much higher than the electron transfer resistance in the semiconductor, which reduces the efficiency of electron transfer in the solar cell, sensitized with longer dye molecules.